POLA ASUH IBU DALAM MENDUKUNG STATUS GIZI BAIK ANAK - Elita Endah Mawarni; Fany Anitarini; Anggi Sudarsono (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
The nutritional status of toddlers is the most important factor that must be considered because toddlerhood is the golden period of development. At the age of toddlers a child's growth is very rapid so that it requires nutritional intake according to its needs, in addition to nutritional intake during toddler growth it also requires good parenting from both parents and family, so that toddler growth and development will be more optimal. The purpose of this study was to determine the relationship between maternal parenting and the nutritional status of toddlers at the Kertosari Health Center in 2021.This study used a correlation design, with a total sampling technique. The number of samples is 48 respondents used in the study. Data was collected using a mother's parenting questionnaire sheet & KMS Observation Sheet.This study showed that most of the respondents had good parenting styles for 27 out of 48 respondents (56.2%) and normal nutritional status for 19 out of 48 respondents (60.4%). Statistical analysis using the Spearman rank test obtained an alpha value of 0.01% meaning 0.01 > 0.084. So there is no significant relationship between Mother's Parenting Style and the Nutritional Status of Toddlers in 2021.Most of the respondents in this study had good parenting styles with normal nutritional status supported by productive age of the mother so that mothers can seek information through social media and have sufficient income to support family needs and nutritional intake for toddlers. In addition, mothers with not busy work status will be able to pay more attention to the growth and development of their toddlers than mothers who don't have much time for their toddlers.